Uma introdução ao estudo das funções matriciais - Silva, Rogério Sullyvan e (2014)
In some areas of mathematics is of great importance to deÖne matrix functions and frequently used functions are polynomials of square matrices. Evaluate a polynomial in square matrices is just a matter of replacing the powers of the matrix considering the constant of the polynomial as a multiple of the identity matrix. In this work the following matrix functions will be studied: exponential, sine and cosine.